Analisis Prediksi Tingkat Kebangkrutan pada PT. Bank Aladin Syariah Tbk Menggunakan Model Z-Score Altman Modifikasi Periode 2021–2024 - Muhammad Firdaus; M. Luthfillah Habibi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of digital banks and the operational losses still experienced by PT Bank Aladin Syariah Tbk necessitate a financial health analysis to assess the potential for financial distress. This study aims to assess the potential bankruptcy level of Bank Aladin for the period 2021–2024 using the Modified Altman Z-Score model. The research method is descriptive quantitative with secondary data from annual financial reports and OJK publications, which are analyzed through four main ratios, namely working capital, retained earnings, earnings before taxes, and equity value to total debt. The results show that the Z-Score values are well above the safety threshold, with the highest value of 17.764 in 2021 and the lowest of 9.422 in 2022, mainly driven by high liquidity and equity strength. Thus, it can be concluded that PT Bank Aladin Syariah Tbk is in the Safe Zone category and does not show any potential for bankruptcy during the research period, although an increase in profitability is still needed.